2012
DOI: 10.1016/j.pep.2012.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Engineering genes for predictable protein expression

Abstract: The DNA sequence used to encode a polypeptide can have dramatic effects on its expression. Lack of readily available tools has until recently inhibited meaningful experimental investigation of this phenomenon. Advances in synthetic biology and the application of modern engineering approaches now provide the tools for systematic analysis of the sequence variables affecting heterologous expression of recombinant proteins. We here discuss how these new tools are being applied and how they circumvent the constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
127
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 81 publications
(97 reference statements)
2
127
0
2
Order By: Relevance
“…Successful overexpression can attain higher expression levels compared to the most natural proteins [10,19].…”
Section: Recombinant Prmentioning
confidence: 99%
“…Successful overexpression can attain higher expression levels compared to the most natural proteins [10,19].…”
Section: Recombinant Prmentioning
confidence: 99%
“…RNAi has been used to target apoptosis (e.g., caspase-3 and 7 [199,200], Bak and Bax [201], requiem [184]); glycosylation (e.g., 1,6-fucosyltransferase [202,203], sialidase [204]); and enzymes such as dihydrofolate reductase (DHFR) [205,206]. Targeting gene expression can be performed using homolog recombination, a variety of nucleases, such as ZFNs, meganucleases, and TALENs [207][208][209][210]. For example, ZFNs have been used to silence expression of Bak and Bax proteins to produce apoptosis-resistant CHO cells [211].…”
Section: Applied Genomics and Cell Line Engineering In Mammalian Exprmentioning
confidence: 99%
“…mRNA secondary structures at the 5′ terminus were shown to impair translation by hindering the ribosomal binding and translational initiation (Kudla et al 2009). Moreover, the GC content and the occurrence of codons rarely used by the production host influenced translation efficiency (Gustafsson et al 2012). It was reported that especially clusters of rare codons have a detrimental effect on translation in Escherichia coli (Kane 1995) causing translational frameshifts (Spanjaard and van Duin 1988), premature translational termination (Rosenberg et al 1993), and amino acid misincorporation (Calderone et al 1996).…”
Section: Introductionmentioning
confidence: 99%